Morski bigos - Folta-Rusin, Anna Kazimiera (Śląskie Studia Polonistyczne, 2012)
The elements of the world contrasted in a novel by Ubertowski do not wonder at each other for the first time, making a surprisingly coherent composition, from which a story about an everyman entangled in the history emerges. It turns out that a talking stork, Mołotow, a pig walking on the beach and Trocki have a lot in common… Bigos, a composition made of leftovers, makes an unusually sublime and harmonious dish after all.